The Role of Islamic Religious Education Teachers in Shaping Students' Communication Ethics - Umar, Muallief; Ummah, Yuli Choirul; Khoiriyah, Imro’atul (IERA, Islamic Education and Research Academy, 2023)
The objectives of this research are as follows: 1. To analyze the model of communication ethics implementation among students at SDI Darush Sholihin. 2. To identify the role of Islamic Religious Education teachers in shaping communication ethics. 3. To describe the supporting and inhibiting factors in the formation of communication ethics. The research method used in this study is qualitative research, which aims to describe a phenomenon in a detailed manner. The type of research employed is a case study, which involves a detailed and in-depth data and information collection process using various methods and techniques. The data collection techniques include observation, interviews, and documentation. Data is analyzed through data collection or display, data reduction, and conclusion drawing. The results of the research indicate that: 1. The Communication Ethics Model includes: Qaulan Sadidan, Qaulan Ma’rufan, Qaulan Baligha, Qaulan Layyina, Qaulan Karima, Qaulan Maisura. 2. The roles undertaken include: Supervisor, who monitors and guides students in practicing good communication; Motivator, who provides support, examples, and role models for good communication; and Transmitter, who conveys the values of communication ethics into the students' daily lives.